Estimated 10-year cardiovascular mortality seriously underestimates overall cardiovascular risk - Jørstad, Harald T (Heart, 2016)
OBJECTIVE: The European Society of Cardiology's prevention guideline suggests that the risk of total (fatal plus non-fatal) cardiovascular disease (CVD) may be calculated from the risk of CVD mortality using a fixed multiplier (3×). However, the proposed multiplier has not been validated. We investigated the ratio of total CVD to CVD mortality in a large population-based cohort. METHODS: CVD mortality and total CVD (fatal plus non-fatal CVD requiring hospitalisation) were analysed using Kaplan-Meier estimates among 24 014 men and women aged 39–79 years without baseline CVD or diabetes mellitus in the prospective population-based European Prospective Investigation of Cancer and Nutrition-Norfolk cohort. CVD outcomes included death and hospitalisations for ischaemic heart disease, heart failure, cerebrovascular disease, peripheral artery disease or aortic aneurysm. The main study outcome was the ratio of 10-year total CVD to 10-year CVD mortality stratified by age and sex. RESULTS: Ten year CVD mortality was 3.9% (900 CVD deaths, 95% CI 3.6% to 4.1%); the rate of total CVD outcomes was 21.2% (4978 fatal or non-fatal CVD outcomes, 95% CI 20.7% to 21.8%). The overall ratio of total CVD to CVD mortality was 5.4. However, we found major differences in this ratio when stratified by gender and age. In young women (39–50 years), the ratio of total CVD to CVD mortality was 28.5, in young men (39–50 years) 11.7. In the oldest age group, these ratios were considerably lower (3.2 in women and 2.4 in men aged 75–79 years). CONCLUSIONS: The relationship between 10-year total CVD and CVD mortality is dependent on age and sex, and cannot be estimated using a fixed multiplier. Using CVD mortality to estimate total CVD risk leads to serious underestimation of risk, particularly in younger age groups, and particularly in women.